(untitled) (Global Journal of Management and Business Research, 2019)
Effort towards retaining committed of regular nonacademic staff has remained a recurrent concern indicating that employees commitment among university workers could have been compromised However even when investigated into more extrinsic and less intrinsic factors are applied to determine the commitment Hence the study approached this gap from job-characteristics dimensions to employee continuance commitment The cross-sectional survey research design was adopted and data collected from 377 regular nonacademic staff using validated and reliable copies of a questionnaire Multiple regression analysis was applied as the inferential statistics Results from multiple regression analysis conducted found that job-characteristics dimensions had a significant effect on employee continuance commitment R 0 726 F 5 371 78 081 p 0 05 Also task identity task significance and feedback had a significant positive effect on continuance commitment On the strength of the statistical findings it was recommended for management emphasize on task identify significance and feedback to enable continuance commitment of non-academic staff